Occupational diseases in the Republic of Srpska from 2011-2020: Occupational disease - Marić, Nada; Peričević Medić, Sonja; Španović, Milorad (Scripta Medica, 2023)
Background/Aim: The importance of occupational diseases is due to their influence on workers’ quality of life and significant socioeconomic problems for the health sector, employers and the state. Occupational diseases are generally not curable but are preventable diseases, so it is extremely important to develop a good system of detection, registration and prevention. Therefore, special attention should be paid to the occupational incidence analysis. Aim of this study was to assess the incidence of occupational diseases in the Republic of Srpska. Methods: The research was conducted as a cross-sectional study based on the obtained data on occupational diseases in the Republic of Srpska for ten years (from 2011 to 2021). Results: In the observed period, 12 cases of occupational diseases were registered in the Republic of Srpska and the incidence was less than 1/100,000 per year. Occupational diseases were diagnosed in: - agriculture, forestry and fishing; - construction and - healthcare and social welfare. Conclusion: The study showed a low incidence of occupational disease and it was observed that certain industrial sectors are particularly undervalued. The current situation regarding occupational diseases in the Republic of Srpska requires an urgent response from the occupational medicine services and the state. It is necessary to initiate procedures as soon as possible to ensure uniformity in the criteria of diagnosis and records of occupational diseases and revision of the list of occupational diseases by the International Labour Organisation. In the future, it is necessary to conduct additional and more detailed research in the field of occupational diseases.